Ameliorative effect of herbacetin against cyclophosphamide-induced nephrotoxicity in rats via attenuation of oxidative stress, inflammation, apoptosis and mitochondrial dysfunction. (29th September 2022) - Ijaz, Muhammad Umar; Mustafa, Shama; Batool, Riffat; Naz, Huma; Ahmed, Hussain; Anwar, Haseeb
Herbacetin (HBN) is a glycosylated flavonoid, which possesses numerous pharmacological properties. Cyclophosphamide (CYC) is a chemotherapeutic drug that adversely affects the kidneys. The present investigation aimed to evaluate the curative potential of HBN against CYC-induced nephrotoxicity. Sprague Dawley rats ( n = 48) were randomly divided into four groups: control (0.1% DMSO + food), CYC (150 mg/kg b.wt.), CYC+HBN (150 + 40 mg/kg b.wt.), and HBN (40mg/kg b.wt.). CYC treatment significantly decreased the activities of antioxidant enzymes such as catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), and glutathione reductase (GSR) while elevating the concentration of reactive oxygen species (ROS) and malondialdehyde (MDA). Treatment with HBN significantly recovered the activity of CAT, SOD, GPx, and GSR while reducing the concentrations of ROS and MDA. Moreover, an increase in the level of renal functional markers, including Urea, creatinine, kidney injury molecule-1 (KIM-1), and neutrophil gelatinase-associated lipocalin (NGAL), and a decrease in creatinine clearance after CYC administration was recovered to control values by HBN treatment. Furthermore, HBN treatment normalized the increased levels of inflammatory markers such as nuclear factor kappa-B (NF-κB), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) after CYC administration. Besides, HBN administration increased the expression of anti-apoptotic markers (Bcl-2) while decreasing the apoptotic markers (Bax and Caspase-3). Furthermore, HBN decreased the activities of tricarboxylic acid (TCA) cycle enzymes (ICDH, αKGDH, SDH, and MDH) as well as renal mitochondrial respiratory-chain complexes (I-IV) and repolarized mitochondrial membrane potential (ΔΨm). Additionally, HBN administration significantly protected against renal histological damage induced by CYC. In conclusion, CYC-induced toxicity was effectively ameliorated by the HBN administration. These results indicate that HBN might be considered as a potential protective agent against nephrotoxicity. The observed protection may be due to its antioxidant, anti-inflammatory, and anti-apoptotic potential.